2015
DOI: 10.3390/w7126667
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Analysis in the Evaluation of Extreme Rainfall Trends and Its Implications on Urban Drainage System Design

Abstract: Future projections provided by climate models suggest that the occurrence of extreme rainfall events will increase and this is evidence that the climate is changing. Because the design of urban drainage systems is based on the statistical analysis of past events, variations in the intensity and frequency of extreme rainfall represent a critical issue for the estimation of rainfall. For this reason, the design criteria of drainage systems should take into account the trends in the past and the future climate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…For example, Arnbjerg-Nielsen (2012) reported that the design intensities in Denmark are projected to increase by 10-50 % for return periods ranging from 2 to 100 years. Therefore, it is important to investigate the performance of drainage systems in a changing environment and to assess the potential urban flooding under various scenarios to achieve better adaptations (Mishra, 2015;Karamouz et al, 2013;Yazdanfar and Sharma, 2015;Notaro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Arnbjerg-Nielsen (2012) reported that the design intensities in Denmark are projected to increase by 10-50 % for return periods ranging from 2 to 100 years. Therefore, it is important to investigate the performance of drainage systems in a changing environment and to assess the potential urban flooding under various scenarios to achieve better adaptations (Mishra, 2015;Karamouz et al, 2013;Yazdanfar and Sharma, 2015;Notaro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In West Africa, shifts in time series of rainfall have been observed: a wet period occurred between 1930 and 1960, a drought from 1970 to 1980 and gradual return of normal rains in the period from 1990 to 2000. Change in precipitation frequency, intensity, duration and consequently on the hydrological cycle has then been notified by many authors [4] [10]. In Senegal, this style of agricultural practice employs 77% of working people and supplies 12.4% of the daily food [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many scientific studies in hydroclimatic field are oriented towards determining the states, the causes and consequences of climate variability and change [2] [3]. According to these studies, climate change is due to increased greenhouse gas concentrations, while trend and shift in runoff time series data are consequence of climate change effects, land use change (urbanization, clearing, deforestation and others) or change in management practice [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the results of [32], by which sub-grid scale convection and intensification phenomena indicate, for Sicily, an increasing trend towards shorter rain durations (about one hour) during the period 1927-2004. Additionally, the increase in the intense precipitation has been recently highlighted in Western Sicily by [33].…”
Section: Transformation In the Standard Normal Distributionmentioning
confidence: 99%